Depression and brain fog as long-COVID mental health consequences: Difficult, complex and partially successful treatment of a 72-year-old patient—A case report - Taube, Maris (Frontiers in Psychiatry, 2023)
SARS-CoV-2 (COVID-19) infection can result in long-term health consequences i.e., long COVID. The clinical manifestations of long COVID include depression, anxiety, brain fog with cognitive dysfunction, memory issues, and fatigue. These delayed effects of COVID-19 occur in up to 30% of people who have had an acute case of COVID-19. In this case report, a 72-year-old, fully vaccinated patient without pre-existing somatic or mental illnesses, or other relevant risk factors was diagnosed with long COVID. Nine months following an acute COVID-19 infection, the patient’s depressive symptoms improved, but memory and concentration difficulties persisted, and the patient remains unable to resume work. These long-term symptoms are possibly linked to micro-hemorrhages detected during examinations of the patient’s brain following COVID-19 infection. Patient treatment was complex, and positive results were attained via antidepressants and non-drug therapies e.g., art, music, drama, dance and movement therapy, physiotherapy, occupational therapy, and psychotherapy.